Novel preparation method of solid electrolyte with high ionic conductivity

The method of mixing lithium source, lanthanum source and fluorine source by wet ball milling, and adding solid phase dispersant to perform a one-step sintering method, solving the problem of excessive lithium and lanthanum in the prior art, and achieving a high ionic conductivity solid state The mass production and industrialization of electrolyte materials have achieved higher ionic conductivity.

CN119320170APending Publication Date: 2025-01-17NORTHEASTERN UNIV CHINA
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411226234.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing solid electrolyte material preparation process has a two-step sintering process, which can easily cause excessive lithium and lanthanum elements, form miscellaneous phases, and it is difficult to achieve mass production of materials with high ionic conductivity.

Method used

A new preparation method is adopted, the lithium source, lanthanum source and fluorine source are mixed by wet ball milling method, solid phase dispersants CTAB and CA are added, and one-step sintering is carried out, and the vacuum tube furnace is used to heat up in the protective atmosphere to optimize Li2−xLa( Preparation process of 1+x)/3Nb2O6F.

Benefits of technology

Massive production of high-ionic conductivity materials with pure phase Li2−xLa(1+x)/3Nb2O6F is achieved, which avoids the formation of heterogeneous phases, improves the industrialization potential of materials, and obtains higher ions than existing reports. Conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320170A_ABST
    Figure CN119320170A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid electrolyte materials, and particularly relates to a novel preparation method of a solid electrolyte with high ionic conductivity. The lithium source, the lanthanum source, the niobium source and the fluorine source are mixed, and the solid-phase dispersing agent is added in the mixing process, so that more uniform mixing is facilitated. According to the preparation method, precursor powder is obtained after mixing, then pure-phase LLNOF powder can be directly obtained through one-step sintering, the difficulty that in an existing reported preparation process scheme, a product obtained through two-step sintering has an impure phase is overcome, the preparation process is simple, and batch production and industrialization are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolyte materials, and in particular relates to a novel preparation method of a solid electrolyte with high ionic conductivity. Background Art

[0002] Solid-state batteries, as a new type of lithium-ion battery using solid electrolytes, have higher energy density and better safety than traditional liquid lithium-ion batteries. This industry is an important part of my country's photovoltaic energy storage, wind power generation, new energy vehicles and other industries, and is the key to promoting green and low-carbon development. 2−x La (1+x) / 3 Compared with existing common solid electrolytes, Nb2O6F has higher lithium ion conductivity and wider electrochemical window while also having better air stability. It is the solid electrolyte material with the greatest commercial potential.

[0003] Scholar Akihisa Aimi in High Li-Ion Conductivity in Pyrochlore-Type SolidElectrolyte Li 2−x La (1+x) / 3 M2O6F (M = Nb, Ta) reported the preparation of pyrochlore-type Li 2−x La (1+x) / 3 Nb2O6F, in this preparation scheme, an excess of LiF was added, and the obtained material had an ionic conductivity of up to 3.9ms / cm.

[0004] The existing reported process for preparing LLNOF is to first prepare LLNO material, then mix the LLNO precursor powder with lithium fluoride and lanthanum fluoride, press and sinter, and obtain flaky LLNOF. This preparation method undergoes a two-step sintering process, and uses lithium fluoride and lanthanum fluoride as fluorine sources, which easily causes excessive lithium and lanthanum elements and forms impurities. Summary of the invention

[0005] In view of the problems in the prior art, the present invention provides a novel preparation method of a solid electrolyte with high ionic conductivity. This material can be used in solid-state batteries as a solid electrolyte, and its high ionic conductivity can fully improve the performance of the battery. Its preparation process is simple and convenient, and it can also be conducive to the large-scale production of such batteries, thereby improving production efficiency and reducing production costs.

[0006] The technical solution of the present invention is: A novel preparation method of a solid electrolyte with high ionic conductivity, wherein the chemical formula of the conductive solid electrolyte is Li 2−x La (1+x) / 3Nb2O6F (0<x≤0.5), the preparation method comprises the following steps: Step 1: Prepare mixed powder: The raw materials of lithium source, lanthanum source, niobium source and fluorine source are weighed according to chemical measurement. Because there will be overflow loss of lithium source and fluorine source in the firing production process, 5% more lithium source and fluorine source are weighed and mixed. The pre-prepared solid phase dispersant is added during the mixing process, and the raw materials are fully mixed by wet ball milling. According to the weighed raw material mass, the reasonable grinding bead size and mass and the mass of the grinding solvent are configured. The ball mill speed is set to 300-600r / min, the stirring time is 100-150min, and the stirring is stopped for 3-10min every 25-60min. After the stirring is completed, the mixed slurry is placed in a drying oven for drying, the temperature is set to 60-125℃, and the drying time is 1-10h. Finally, the dried powder is ground to obtain a fully mixed powder. Step 2: Preparation of LLNOF solid electrolyte powder: The powder ground in step 1 is placed in an ark and put into a vacuum tube furnace; first, a vacuum pump is used to evacuate the air in the vacuum tube furnace for 3 to 10 minutes, and then a protective atmosphere is introduced into the vacuum tube furnace, and then the temperature is increased at 0.5 to 5°C / min to 60 to 200°C, and the temperature is kept for 0.5 to 6 hours, and finally the temperature is increased to 900 to 1250°C at 0.5 to 6°C / min, and the temperature is kept for 2 to 12 hours to obtain a pure phase LLNOF powder, which has high ionic conductivity.

[0007] Furthermore, in the above-mentioned novel preparation method of a solid electrolyte with high ionic conductivity, in step 1, the solid phase dispersant is prepared by CTAB and CA, wherein the ratio of CTAB to CA is in the range of 1:10 to 1:4.

[0008] Furthermore, in the above-mentioned novel preparation method of a solid electrolyte with high ionic conductivity, the added amount of the solid phase dispersant in step 1 is 1% to 5% of the total weight of the lithium source, lanthanum source, niobium source and fluorine source.

[0009] Furthermore, in the above-mentioned novel preparation method of a solid electrolyte with high ionic conductivity, the lithium source in step 1 includes lithium carbonate, lithium hydroxide monohydrate, lithium acetate, and lithium oxalate; the lanthanum source includes lanthanum hydroxide, lanthanum trioxide, and lanthanum acetate; the niobium source includes lithium niobate and niobium pentoxide; and the fluorine source includes ammonium fluoride and lithium fluoride.

[0010] Furthermore, in step 1 of the above-mentioned novel preparation method of a solid electrolyte with high ionic conductivity, the weight ratio of the total weight of the lithium source, lanthanum source, niobium source and fluorine source to the weight of the grinding solvent is in the range of 1:3 to 1:6, and the grinding solvent is deionized water, methanol, ethanol, isopropanol, n-butanol or acetone.

[0011] Furthermore, in step 1 of the above-mentioned novel preparation method for a solid electrolyte with high ionic conductivity, the diameter of the grinding beads is 1 mm, 3 mm, 5 mm, 6 mm or 10 mm, and the material thereof is aluminum oxide, zirconium oxide or agate. The ratio of the mass of the grinding beads to the total weight of the lithium source, lanthanum source, niobium source and fluorine source is 10:1~5:1.

[0012] Furthermore, the protective atmosphere used in step 2 of the above-mentioned novel preparation method of a solid electrolyte with high ionic conductivity is argon or nitrogen.

[0013] The ionic conductivity of the above LLNOF solid electrolyte powder was tested: Take 0.1~5g of the above LLNOF material and add PVA to mix thoroughly. Use a mold with a diameter of 10mm~15mm, apply a pressure of 65~95MPa in a desktop powder tablet press, maintain the pressure for 10~20min, and then demold to obtain a thin sheet. Place the above thin sheet in a sintering furnace and heat it to 900~1300℃ at 2~5℃, and keep it warm for 12~20h. You can get a ceramic sheet. Use 1500 mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of the LLNOF material.

[0014] The technical principle of the present invention is: By mixing the lithium source, lanthanum source, niobium source and fluorine source, adding a solid phase dispersant during the mixing process helps to mix more evenly. After mixing, the precursor powder is obtained. The LLNOF target product prepared by the technical solution is easier to mass produce, which is conducive to the industrialization of the material. The solid phase dispersant is: CTAB (hexadecyltrimethylammonium bromide) and CA (citric acid). There is an electrostatic attraction between the cationic group of CTAB and CA. There is also an electrostatic attraction between the cations in the lithium source, lanthanum source, niobium source and fluorine source and CA. CTAB is a commonly used surfactant that can effectively change the surface tension of the solution, so that inorganic materials such as lithium source, lanthanum source, niobium source and fluorine source are mixed more evenly. Using these interaction forces, the uniformity of the precursor mixing can be effectively controlled by adjusting the concentrations of CTAB and CA. Thereby avoiding the two-step sintering method reported in the existing literature, which is more conducive to the industrialization of the material.

[0015] Advantages and beneficial effects of the present invention: The LLNOF powder prepared by the present invention can directly obtain pure-phase LLNOF powder through one-step sintering through process optimization, thus overcoming the difficulty of the existing reported preparation process scheme that the product obtained by two-step sintering contains impurities, and the preparation process is simple, which is convenient for mass production and industrialization.

[0016] Existing scholars reported that the LLNOF prepared by adding excess LiF to make the surface of the LLNOF particles have amorphous LiF after preparation, so that its ionic conductivity can reach up to 3.9ms / cm. In this technical solution, only the optimization process of adding an appropriate amount of LiF is used to obtain LLNOF with higher ionic conductivity than the existing reports. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 These are the XRD diagrams of the solid electrolytes of Example 1, Example 5, Example 8, Example 10, Comparative Example 1, Comparative Example 3, and Comparative Example 5. DETAILED DESCRIPTION

[0018] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention.

[0019] Example 1

[0020] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.046 g of CTAB and 0.367 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 2.2 g of La(OH)3, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of ethanol is added; then 70 g of 3 mm diameter zirconium oxide ball milling beads are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0021] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0022] The dried mixed powder was ground using a mortar.

[0023] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0024] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0025] Example 2

[0026] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.044 g of CTAB and 0.353 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 1.89 g of La2O3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of ethanol is added; then 70 g of 3 mm diameter zirconium oxide ball milling beads are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 500 r / min, the stirring time is 155 min, and the stirring is stopped for 5 min after every 35 min.

[0027] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0028] The dried mixed powder was ground using a mortar.

[0029] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0030] First, the temperature was raised to 120°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0031] 3. Performance Test Same as Example 1 Example 3

[0032] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.046 g of CTAB and 0.368 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.22 g of LiOH·H2O, 2.203 g of La(OH)3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 500 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0033] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 3 h.

[0034] The dried mixed powder was ground using a mortar.

[0035] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0036] First, the temperature was raised to 110°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.8 La 0.4 Nb2O6F.

[0037] Example 4

[0038] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.044 g of CTAB and 0.354 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.22 g of LiOH·H2O, 1.89 g of La2O3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of methanol is added; then 70 g of zirconia ball milling beads with a diameter of 5 mm are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 500 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0039] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 6 h.

[0040] The dried mixed powder was ground using a mortar.

[0041] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0042] First, the temperature was raised to 128°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0043] Example 5

[0044] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.045 g of CTAB and 0.36 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.346 g of CH3COOLi, 1.89 g of La2O3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 6 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 500 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0045] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 3 h.

[0046] The dried mixed powder was ground using a mortar.

[0047] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0048] First, the temperature was raised to 150°C at a rate of 3°C / min and kept at that temperature for 2h. Then, the temperature was raised to 1100°C at a rate of 3°C / min and kept at that temperature for 6h to obtain pure Li 1.59 La 0.47 Nb2O6F.

[0049] Example 6

[0050] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.06 g of CTAB and 0.36 g of CA were weighed according to a 1:6 ratio to prepare a solid phase dispersant, and then 0.346 g of CH3COOLi, 2.20 g of La(OH)3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of ethanol is added; then 70 g of agate ball milling beads with a diameter of 6 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 500 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0051] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 3 h.

[0052] The dried mixed powder was ground using a mortar.

[0053] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0054] First, the temperature was raised to 120°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 3h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0055] Example 7

[0056] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.083 g of CTAB and 0.334 g of CA were weighed according to a 1:4 ratio to prepare a solid phase dispersant, and then 0.267 g of Li2C2O4, 2.20 g of La(OH)3, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of ethanol is added; then 70 g of agate ball milling beads with a diameter of 6 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0057] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 3 h.

[0058] The dried mixed powder was ground using a mortar.

[0059] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0060] First, the temperature was raised to 120°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 4h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0061] Example 8

[0062] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: First, 0.051 g of CTAB and 0.407 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.952 g of Li2C2O4, 2.339 g of C6H9LaO6, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of isopropanol is added; then 70 g of agate ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0063] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 5 h.

[0064] The dried mixed powder was ground using a mortar.

[0065] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0066] First, the temperature was raised to 120°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 4h to obtain pure Li 1.89 La 0.37 Nb2O6F.

[0067] Example 9

[0068] This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.055 g of CTAB and 0.439 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.346 g of CH3COOLi, 3.666 g of C6H9LaO6, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of n-butanol is added; then 70 g of agate ball milling beads with a diameter of 10 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0069] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 90 °C and the drying time was 3 h.

[0070] The dried mixed powder was ground using a mortar.

[0071] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then nitrogen was introduced into the vacuum tube furnace.

[0072] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 8h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0073] Example 10 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.068 g of CTAB and 0.406 g of CA were weighed according to a 1:6 ratio to prepare a solid phase dispersant, and then 0.441 g of LiOH·H2O, 3.16 g of C6H9LaO6, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 45 ml of ethanol is added; then 70 g of agate ball milling beads with a diameter of 3 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0074] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 3 h.

[0075] The dried mixed powder was ground using a mortar.

[0076] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0077] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 4h to obtain pure Li 1.5 La 0.5 Nb2O6F.

[0078] Embodiment 11 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.054 g of CTAB and 0.432 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 3.666 g of C6H9LaO6, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 45 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 1 mm are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0079] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 4 h.

[0080] The dried mixed powder was ground using a mortar.

[0081] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0082] First, the temperature was raised to 110°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 4h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0083] Example 12 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.06 g of CTAB and 0.477 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.97 g of Li2CO3, 3.666 g of C6H9LaO6, 5.316 g of Nb2O5 and 0.778 g of NH4F were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of ethanol is added; then 70 g of agate ball milling beads with a diameter of 1 mm are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0084] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 60 °C and the drying time was 4 h.

[0085] The dried mixed powder was ground using a mortar.

[0086] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0087] First, the temperature was raised to 110°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li1.25 La 0.58 Nb2O6F.

[0088] Example 13 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.05 g of CTAB and 0.403 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 1.303 g of Li2CO3, 1.671 g of La(OH)3, 5.316 g of Nb2O5 and 0.778 g of NH4F were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of acetone is added; then 70 g of 3 mm diameter zirconium oxide ball milling beads are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0089] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 55 °C and the drying time was 4 h.

[0090] The dried mixed powder was ground using a mortar.

[0091] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0092] First, the temperature was raised to 110°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.68 La 0.44 Nb2O6F.

[0093] Embodiment 14 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.05 g of CTAB and 0.398 g of CA were weighed according to a 1:8 ratio to prepare a solid phase dispersant, and then 0.97 g of Li2CO3, 1.89 g of La2O3, 5.316 g of Nb2O5 and 0.778 g of NH4F were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of acetone is added; then 70 g of agate ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0094] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 55 °C and the drying time was 4 h.

[0095] The dried mixed powder was ground using a mortar.

[0096] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then nitrogen was introduced into the vacuum tube furnace.

[0097] First, the temperature was raised to 110°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 4h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0098] Embodiment 15 This embodiment provides a novel preparation method of a solid electrolyte with high ionic conductivity, comprising the following steps: 1. Preparation of mixed powder First, 0.042 g of CTAB and 0.424 g of CA were weighed according to a 1:10 ratio to prepare a solid phase dispersant, and then 1.337 g of Li2C2O4, 1.89 g of La2O3, 5.316 g of Nb2O5 and 0.778 g of NH4F were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 50 ml of acetone is added; then 70 g of zirconia ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0099] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 55 °C and the drying time was 6 h.

[0100] The dried mixed powder was ground using a mortar.

[0101] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then nitrogen was introduced into the vacuum tube furnace.

[0102] First, the temperature was raised to 128°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain pure Li 1.25 La 0.58 Nb2O6F.

[0103] The above fifteen embodiments are subjected to performance tests: Ionic conductivity test: Take 1g of the above LLNOF material and add 1ml PVA to stir and mix thoroughly. Use a mold with a diameter of 10mm, apply a pressure of 75MPa in a desktop powder tablet press, and demold after holding the pressure for 10min to obtain a thin sheet. Place the above thin sheet in a sintering furnace in an air atmosphere, and heat it from 3°C to 1200°C, and keep it warm for 6h to obtain a ceramic sheet. Use 1500 mesh sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L of the ceramic sheet, use an ion sputtering instrument to evaporate gold blocking electrodes, and use AC impedance to test the ionic conductivity of the LLNOF material.

[0104] Comparative Example 1 The method for preparing LLNOF solid electrolyte powder in this comparative example comprises the following steps: 1. Preparation of mixed powder First, 0.138 g of CTAB and 0.275 g of CA were weighed according to a 1:2 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 2.2 g of La(OH)3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 10 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0105] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0106] The dried mixed powder was ground using a mortar.

[0107] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0108] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1100°C at 3°C / min and kept at this temperature for 6h to obtain Li 1.25 La 0.58 Nb2O6F.

[0109] Comparative Example 2 The method for preparing LLNOF solid electrolyte powder in this comparative example comprises the following steps: 1. Preparation of mixed powder First, 0.024 g of CTAB and 0.389 g of CA were weighed according to a 1:16 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 2.2 g of La(OH)3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of ethanol is added; then 70 g of agate ball milling beads with a diameter of 1 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0110] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0111] The dried mixed powder was ground using a mortar.

[0112] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a tube furnace to be sintered in an air atmosphere.

[0113] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1200°C at 3°C / min and kept at this temperature for 6h to obtain Li 1.25 La 0.58 Nb2O6F.

[0114] Comparative Example 3 The method for preparing LLNOF solid electrolyte powder in this comparative example comprises the following steps: 1. Preparation of mixed powder First, 0.029 g of CTAB and 0.464 g of CA were weighed according to a 1:16 ratio to prepare a solid phase dispersant, and then 0.214 g of Li2C2O4, 3.792 g of C6H9LaO6, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 80 ml of ethanol is added; then 70 g of alumina ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0115] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0116] The dried mixed powder was ground using a mortar.

[0117] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder is placed in an ark, and the ark is placed in a vacuum tube furnace; first, a vacuum pump is used for 5 minutes to exhaust the air in the vacuum tube furnace.

[0118] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1350°C at 3°C / min and kept at this temperature for 6h to obtain Li 1.2 La 0.6 Nb2O6F.

[0119] Comparative Example 4 The method for preparing LLNOF solid electrolyte powder in this comparative example comprises the following steps: 1. Preparation of mixed powder First, 0.027 g of CTAB and 0.424 g of CA were weighed according to a 1:16 ratio to prepare a solid phase dispersant, and then 1.07 g of Li2C2O4, 2.086 g of C6H9LaO6, 5.316 g of Nb2O5 and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 80 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 3 mm are added and mixed thoroughly by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0120] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0121] The dried mixed powder was ground using a mortar.

[0122] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used for 5 minutes to exhaust the air in the vacuum tube furnace and nitrogen was introduced.

[0123] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1350°C at 3°C / min and kept at this temperature for 6h to obtain Li2La. 0.33 Nb2O6F.

[0124] Comparative Example 5 The method for preparing LLNOF solid electrolyte powder in this comparative example comprises the following steps: 1. Preparation of mixed powder First, 0.138 g of CTAB and 0.275 g of CA were weighed according to a 1:2 ratio to prepare a solid phase dispersant, and then 0.194 g of Li2CO3, 2.203 g of La(OH)3, 5.316 g of Nb2O5, and 0.545 g of LiF were weighed according to the stoichiometric ratio; After the above reagents are fully mixed, 40 ml of ethanol is added; then 70 g of zirconia ball milling beads with a diameter of 5 mm are added and the mixture is fully mixed by wet ball milling. The ball mill speed is set to 600 r / min, the stirring time is 135 min, and the stirring is stopped for 5 min after every 30 min.

[0125] After wet ball milling, the mixed slurry was placed in a drying oven for drying. The temperature was set to 65 °C and the drying time was 3 h.

[0126] The dried mixed powder was ground using a mortar.

[0127] 2. Preparation of LLNOF solid electrolyte powder The obtained mixed powder was placed in an ark, and the ark was placed in a vacuum tube furnace; first, a vacuum pump was used to evacuate the air in the vacuum tube furnace for 5 minutes, and then argon gas was introduced into the vacuum tube furnace.

[0128] First, the temperature was raised to 100°C at 3°C / min and kept at this temperature for 2h. Then, the temperature was raised to 1200°C at 3°C / min and kept at this temperature for 6h to obtain Li 1.25 La 0.58 Nb2O6F.

[0129] Comparative Example 6 The commercially purchased LLZO powder was taken out and put into a mortar for thorough grinding.

[0130] Comparative Example 7 The commercially purchased LLTO powder was taken out and put into a mortar for thorough grinding.

[0131] Comparative Example 8 The commercially purchased LATP powder was taken out and put into a mortar for thorough grinding.

[0132] The above eight comparison ratios were tested for performance: Ionic conductivity test: Take 1g of the above LLNOF and the ground LLZO, LLTO and LATP materials and add 1ml PVA to each and stir thoroughly. Use a mold with a diameter of 10mm, apply a pressure of 75MPa in a desktop powder tablet press, and demold after holding the pressure for 10min to obtain a thin sheet. Place the above thin sheet in a sintering furnace in an air atmosphere, and heat it from 3°C to 1200°C, and keep it warm for 6h to obtain a ceramic sheet. Use 1500-grit sandpaper moistened with alcohol to gently polish the surface of the above ceramic sheet according to the cross-cross method to remove surface impurities and ensure that the thickness of the electrolyte is uniform at all positions. Use a vernier caliper to measure the thickness L of the ceramic sheet, use an ion sputtering instrument to evaporate the gold blocking electrode, and use AC impedance to test the ionic conductivity of the LLNOF material.

[0133] The performance test results of the above examples and comparative examples are shown in Table 1: Table 1 Performance test results Ionic conductivity (mS / cm) Example 1 3.93 Example 2 3.56 Example 3 3.27 Example 4 3.33 Example 5 3.81 Example 6 4.10 Example 7 4.13 Example 8 3.57 Example 9 4.23 Example 10 4.15 Embodiment 11 3.61 Example 12 3.15 Example 13 3.12 Embodiment 14 3.94 Embodiment 15 3.84 Comparative Example 1 0.17 Comparative Example 2 0.34 Comparative Example 3 0.16 Comparative Example 4 0.65 Comparative Example 5 0.10 Comparative Example 6 0.29 Comparative Example 7 0.18 Comparative Example 8 0.34 Data description: Li 2−x La (1+x) / 3 After process optimization, the ionic conductivity of Nb2O6F (0<x≤0.5) material is significantly improved.

[0134] Figure 1 Li prepared by the optimized process 2−x La (1+x) / 3 The XRD phase of Nb2O6F (0<x≤0.5) material is relatively pure. Figure 1 There are impurity phases in the XRD patterns of the various comparative examples shown.

Claims

1. A novel method for preparing a solid electrolyte with high ionic conductivity, characterized in that: The chemical formula of the conductive solid electrolyte is Li 2−x La (1+x) / 3 Nb2O6F (0<x≤0.5), the preparation method comprises the following steps: Step 1: Prepare mixed powder: The raw materials of lithium source, lanthanum source, niobium source and fluorine source are weighed and mixed according to chemical measurement, and a pre-prepared solid phase dispersant is added during the mixing process, and the raw materials are fully mixed by wet ball milling, and a reasonable grinding bead size and mass and a grinding solvent mass are configured according to the weighed raw material mass, and the ball mill speed is set to 300-600 r / min, the stirring time is 100-150 min, and the stirring is stopped for 3-10 min every 25-60 min; after the stirring is completed, the mixed slurry is placed in a drying oven for drying, the temperature is set to 60-125°C, and the drying time is 1-10 h; finally, the dried powder is ground to obtain a fully mixed powder; Step 2: Preparation of LLNOF solid electrolyte powder: The powder ground in step 1 is placed in an ark and put into a vacuum tube furnace; first, a vacuum pump is used to evacuate the air in the vacuum tube furnace for 3 to 10 minutes, and then a protective atmosphere is introduced into the vacuum tube furnace, and then the temperature is increased at 0.5 to 5°C / min to 60 to 200°C, and the temperature is kept for 0.5 to 6 hours, and finally the temperature is increased to 900 to 1250°C at 0.5 to 6°C / min, and the temperature is kept for 2 to 12 hours to obtain a pure phase LLNOF powder, which has high ionic conductivity.

2. A novel preparation method of a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: In step 1, the solid phase dispersant is prepared from CTAB and CA, wherein the ratio of CTAB to CA is in the range of 1:10 to 1:

4.

3. A novel preparation method of a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: The amount of the solid phase dispersant added in step 1 is 1% to 5% of the total weight of the lithium source, lanthanum source, niobium source and fluorine source.

4. A novel preparation method of a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: The lithium source in step 1 includes lithium carbonate, lithium hydroxide monohydrate, lithium acetate, and lithium oxalate; the lanthanum source includes lanthanum hydroxide, lanthanum trioxide, and lanthanum acetate; the niobium source includes lithium niobate and niobium pentoxide; and the fluorine source includes ammonium fluoride and lithium fluoride.

5. A novel preparation method of a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: In step 1, the total weight ratio of the lithium source, lanthanum source, niobium source and fluorine source to the grinding solvent is in the range of 1:3 to 1:6, and the grinding solvent is deionized water, methanol, ethanol, isopropanol, n-butanol or acetone.

6. A novel preparation method of a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: In step 1, the diameter of the grinding beads is 1 mm, 3 mm, 5 mm, 6 mm or 10 mm, and the material thereof is alumina, zirconia or agate. The ratio of the mass of the grinding beads to the total weight of the lithium source, lanthanum source, niobium source and fluorine source is 10:1 to 5:

1.

7. A novel method for preparing a solid electrolyte with high ionic conductivity according to claim 1, characterized in that: The protective atmosphere used in step 2 is argon or nitrogen.

Citation Information

Cited By

  • Method for preparing pyrochlore oxyfluoride solid electrolyte by one-step solid phase method

    CN120432628A

  • Method for preparing pyrochlore-type oxyfluoride solid-state electrolyte by one-step solid phase method

    CN120432628B

  • Two-phase oxyfluoride electrolyte material and preparation method and application thereof

    CN120698500A

  • Oxyfluoride solid electrolyte and preparation method and application thereof

    CN120709482A

  • Pyrochlore type LLNOF solid electrolyte and preparation method and application thereof

    CN122455959A